MOTION GRAPHICS SEBAGAI TEKNIK KOMUNIKASI DALAM IKLAN DI MEDIA SOSIAL - Rahmadieni, Noviarizky Gamma; J. A. Wempi (Jurnal Spektrum Komunikasi, 2025)
In the current overly saturated era, marketers struggle with audience engagement and are forced to compete for audience attention. This study analyzes the impact of motion graphics as an advertising strategy in social media marketing, emphasizing its potential to attract attention and convey even the most complicated ideas in an easy-to-understand format. Unlike previous research, this study captures industry’s practitioners’ insights to explore the strategically advanced use of motion graphics for younger, more visually-oriented and digitally proficient audience. The results show that motion graphics, often perceived as simplistic design elements, offer powerful storytelling that enhances brand and audience connection, increasing branding and audience engagement. Practical applications can assist advertisers in formulating optimally clear and creative strategies by integrating motion graphics into advertising. Additionally, this work serves as a base for later research to broaden the scope of industry analysis and examine the sustainable impact of motion graphics on digital marketing efforts.